2020
DOI: 10.3389/fonc.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Hematological Biomarkers as Reliable Indicators of Soft Tissue Sarcoma Prognosis

Abstract: Background: Several recent studies have reported the reliable prognostic effect of hematological biomarkers in various tumors. Yet, the prognostic value of these hematological markers in soft tissue sarcoma (STS) remains inconclusive. Thus, the aim of this meta-analysis was to check the effect of hematological markers on the prognosis of STS. Methods: We systematically searched for relevant papers published before October 2019 in the PubMed and EMBASE databases. Overall survival (OS) and disease-specific survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
(108 reference statements)
0
22
0
1
Order By: Relevance
“…In addition, accumulating studies have demonstrated that peripheral blood test parameters play a remarkable role in the prognosis of various malignant tumors, such as lung cancer, gastric cancer, and soft tissue sarcoma, as well as GBM. [31][32][33] Unlike genetic biomarkers, preoperative hematological markers, which are detected via noninvasive procedures and are more cost-effective, can be easily obtained from routine blood tests. In the present study, we included 194 homogenous IDH-wt GBM patients to assess preoperative risk factors for early death.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accumulating studies have demonstrated that peripheral blood test parameters play a remarkable role in the prognosis of various malignant tumors, such as lung cancer, gastric cancer, and soft tissue sarcoma, as well as GBM. [31][32][33] Unlike genetic biomarkers, preoperative hematological markers, which are detected via noninvasive procedures and are more cost-effective, can be easily obtained from routine blood tests. In the present study, we included 194 homogenous IDH-wt GBM patients to assess preoperative risk factors for early death.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and meta-analyses have reported the prognostic role of different inflammatory markers in soft tissue sarcomas (STSs) [ 41 , 42 ]. Elevated NLR and PLR and reduced LMR were demonstrated to be correlated with poor clinical outcomes in patients with STS [ 43 , 44 ]. However, most studies have analyzed STSs together with osteoblastic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a series of studies have reported that many inflammation-based markers were directly related to poor prognosis or post-operative complications in patients with hip fracture, including prognostic nutritional index ratio (PNI) [ 9 ], CRP/PNI ratio [ 10 ], and neutrophil-to-lymphocyte ratio (NLR) [ 11 , 12 ]. Platelet-to-lymphocyte ratio (PLR), a novel marker of systemic inflammation, has been reported to be closely related to the prognosis of many diseases, such as inflammatory diseases [ 13 ], cardiovascular disease [ 14 ], and various malignancies [ 15 17 ], even in the 2019-novel coronavirus disease (COVID-19) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%